The Positive Impact of Teams Games Tournament Learning Model Assisted with Video Media on Students’ Mathematics Learning Outcomes - Puspita Dewi, Ida Ayu Kadek Sri; Arini, Ni Wayan (Journal of Education Technology, 2020)
The low of Mathematics learning outcomes of the fifth-grade students are the main problem in this study. It is because the teacher has not implemented a learning model that can enable students in the learning process, the lack of use of media in the learning process provided by the teacher, students study Mathematics rarely, and the lack of concentration in receiving Mathematics. This study aimed to determine the effect of the video media assisted Teams Games Tournament (TGT) learning model on the Mathematics learning outcomes of the fifth-grade students. This research was a quasi-experimental with using non-equivalent post-test only control group design. The population of this research was 137 students. This study applied an intact group technique so the research sample of fifth grade students was 52 students. The students’ Mathematics learning outcomes were collected by using an objective test method through 24 multiple choice questions. The research hypothesis was tested using t-test. Based on the results of data analysis, the researcher obtained tcount = 14,354 > ttable = 2,021 (at a significance level 5%). The result of hypothesis test indicated that there was a significant difference on students’ Mathematics learning outcomes. Thus, it can be concluded that the video media assisted Teams Games Tournament (TGT) significantly influences the mathematics learning outcomes.